2014
DOI: 10.1007/s00253-014-5695-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the insertion events of IS2 transposition are biased towards abrupt compositional shifts in target DNA and modulated by a diverse set of culture parameters

Abstract: Insertion specificity of mobile genetic elements is a rather complex aspect of DNA transposition, which, despite much progress towards its elucidation, still remains incompletely understood. We report here the results of a metaanalysis of IS2 target sites from genomic, phage, and plasmid DNA and find that newly acquired IS2 elements are consistently inserted around abrupt DNA compositional shifts, particularly in the form of switch sites of GC skew. The results presented in this study not only corroborate our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, IS Kpn26 was adjacent to mcr-1 in isolates ZJ148 and ZJ1653, and several other IS elements such as IS 2 , IS 609 , IS 683 , IS 1294 , IS 150 , and IS Sen6 were found in the mcr-1 -positive contigs but not in locations immediately proximal to mcr-1 . Whether these IS elements could contribute to the mobilization of mcr-1 remains unknown, but their presence would enhance the transmission of mcr-1 and facilitate its close association with other antibiotic resistance genes as seen in isolates ZJ134, ZJ33, ZJ487, ZJ26, and ZJ71 ( 41 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IS Kpn26 was adjacent to mcr-1 in isolates ZJ148 and ZJ1653, and several other IS elements such as IS 2 , IS 609 , IS 683 , IS 1294 , IS 150 , and IS Sen6 were found in the mcr-1 -positive contigs but not in locations immediately proximal to mcr-1 . Whether these IS elements could contribute to the mobilization of mcr-1 remains unknown, but their presence would enhance the transmission of mcr-1 and facilitate its close association with other antibiotic resistance genes as seen in isolates ZJ134, ZJ33, ZJ487, ZJ26, and ZJ71 ( 41 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study reported the contamination by 1.3 kb IS2 in a pDNA vaccine candidate, with pVAX1 as the backbone, between the kanamycin resistance cassette and BGH polyA signal [35]. The frequency at which such undesirable events could be triggered relies on the presence of switch sites of GC and AT skews (ssGCs and ssATs) in pDNA, as well as on the time, cell density and mode of cultivation [36]. Complete sequencing of the plasmids from the master cell bank and from the conditions assessed in this work demonstrated that DOT availability did not altered plasmid sequence fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…GC-skew is known to be a non-trivial property that on occasion reflect the presence of certain genomic features. For example, a change of polarity (the sign) of GC-skew indicates such features as the origin of replication [36] and the site of mobile genetic element insertion [37]. The consistently higher mean GC-skew that we observe in circular viruses compared to linear viruses may have a role in structural configuration given that GC-skew in this case is a property that discriminates between two topological classes.…”
Section: Resultsmentioning
confidence: 90%